Development of Evaluation Tools Using the Quizizz Application in PAI Learning in Grade 8 Junior High School Plus Al-Aqsa Modern Cottage - Saeful Basyari, Zen Anwar; Safwanady Nugraha, Mulyawan (Yayasan Mentari Madani, 2024)
The assessment of learning in numerous schools, whether conducted through written or oral means, often induces a sense of monotony among students with the existing evaluation system. In the evolution of assessment methods, various tools have been introduced, one of which is the Quizizz system utilizing the quizizz program. This article seeks to examine the implementation of assessment tools within the realm of Islamic Religious Education (PAI) by employing the Quizizz application. It investigates whether there are discernible transformations in students and if the tool serves as a motivational factor during the evaluation process, or conversely, if its use hampers the effectiveness of students or the evaluation system. Employing a qualitative approach and field research methods, this study was conducted specifically within the 8th-grade classroom of SMP Plus Al Aqsa. The findings indicate that the integration of Quizizz into PAI learning was not only effective but also succeeded in inspiring students, leading to enhancements in their examination performance